Effect of Angiotensin-Neprilysin Versus Renin-Angiotensin System Inhibition on Renal Outcomes: A Systematic Review and Meta-Analysis - Ying Xu; Ying Xu; Ying Xu; Ying Xu; Ying Xu; Yang Chen; Yang Chen; Yang Chen; Yang Chen; Jia Wei Zhao; Chao Li; Chao Li; et al. (Frontiers Media S.A., 2021)
Aims: We aim to perform a systematic review and meta-analysis examining randomized controlled trials assessing the efficacy and safety of sacubitril/valsartan in patients on renal outcomes, in comparison with the renin-angiotensin-aldosterone system inhibitor (RAASi).Methods: Eligible studies were retrieved on MEDLINE, EMBASE, and Cochrane until September 2021. The primary outcome was the incidence of renal impairment, which was defined as the composite of increases in serum creatinine by >0.3 mg/dl and/or a reduction in eGFR ≥25%, development of ESRD, or renal death. We pooled relative risks (RRs) with 95% confidence intervals (CIs) or the mean difference with 95% CIs for the variables.Results: Our search yielded 10 randomized controlled trials with a total of 18,362 patients. Compared with RAASi treatment, patients treated with sacubitril/valsartan had lower incidence of composite renal impairment (10 studies, 18,362 patients, RR 0.84; 95% CI 0.72-0.96, p = 0.01; I2 = 22%), ESRD development (3 studies, 13,609 patients, RR 0.53; 95% CI 0.30-0.96, p = 0.03; I2 = 0%), drug discontinuation due to renal events (4 studies, 9,995 patients, RR 0.58; 95% CI 0.40-0.83, p = 0.003; I2 = 47%), severe hyperkalemia (6 studies, 16,653 patients, RR 0.80; 95% CI 0.68-0.93, p = 0.01; I2 = 25%) and a slower eGFR decline (4 studies, 13,608 patients, WMD 0.56; 95% CI 0.36-0.76, p < 0.00001; I2 = 65%). Subgroup analysis demonstrated that sacubitril/valsartan was associated with a lower incidence of renal impairment in patients with heart failure and preserved ejection fraction (HFpEF), but not in those with heart failure and reduced ejection fraction (HFrEF). The superior renal function preservation of sacubitril/valsartan treatment was not associated with different baseline eGFR levels and follow-up duration. There was a smaller increase in the change in the urine albumin-to-creatinine ratio (UACR) (3 studies, 9,114 patients, SMD 0.06; 95% CI 0.02-0.10, p = 0.003; I2 = 14%) with sacubitril/valsartan treatment. However, patients with heart failure appeared to have increased microalbuminuria, not patients without HF (p = 0.80 for interaction).Conclusion: Sacubitril/valsartan was associated with a lower incidence of composite renal impairment especially in patients with HFpEF, but higher microalbuminuria in patients with heart failure (both HFrEF and HFpEF) compared with RAASi. The lower incidence of severe hyperkalemia and drug discontinuation due to renal events in patients with sacubitril/valsartan treatment demonstrated its superior safety compared with RAASi.